Upaya Penerapan Manajemen Pengetahuan dI Perpustakaan STIKES ALifah Padang - Husna, Nikmatul; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2019)
AbstractIn this paper, we discuss the implementation of knowledge management in the Alifah Padang STIKes Library. The writing of this paper aims to describe: (1) the application of technology in the Alifah Padang STIKes Library; (2) cultural changes that occur in the Alifah Padang STIKes Library; (3) knowledge sharing activities in the Alifah Padang STIKes Library; (4) knowledge management socialization at Alifah Padang STIKes Library. This study uses a descriptive method with a qualitative approach, which is collecting data by observing and interviewing 5 visitors and 1 librarian at the Alifah Padang STIKes Library. Based on the analysis of the data described earlier, it can be concluded the following matters. First, the application of information technology in the Alifah STIKes Library is applied to the field of information processing activities using the SIMPUS application and information retrieval fields by utilizing online catalogs. Second, the cultural changes that occurred in the STIKes Library were seen from the changes in the organizational structure of the Alifah STIKes Library, which was based on the level of human resources and expertise in managing the library.Â Second, the cultural changes that occurred in the STIKes Library were seen from the changes in the organizational structure of the Alifah STIKes Library, which was based on the level of human resources and expertise in managing the library. Third, the form of knowledge sharing activities in the Alifah STIKes Library was carried out by sharing knowledge between Alifah STIKes library officers on issues in library management, establishing cooperative relations with 9 university libraries in West Sumatra in the field of complementary library materials, and participating in training activities at Bina institutions. Jakarta Library. Fourth, Knowledge management socialization in the Alifah STIKes Library in terms of the socialization of the results of the meeting which was decided by the Chairperson of Alifah STIKes based on mutual agreement of the meeting members, by delivering the results of the meetings conducted hierarchically through superiors to subordinates in an oral and written form thoroughly.Keywords: knowledge management; implementation; library